APLIKASI PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN BRAILLE ANAK TUNANETRA TKLB - DIANITA, LENY (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Blind people have barriers to the sense of vision. The barriers of the function of the sense of vision affect the teaching and learning activities. Especially of the blind children of TKLB. These children have problem in recognizing numbers. Blind children need creative and appropriate learning, Such as contextual learning in which the teachers link the learning materials with the children’s environment. The objective of this study is to determine whether or not there is an effect of the implementation of contextual learning on the ability to recognize braille numbers of the blind children. This study used quantitative methods, namely pre-Experimental Design and One using Group Pre-test Post-Test Design. The data were collected using test. The data were analyzed using non-parametric statistics, sign test with n=6 and α=5%. The results show that the average score of pre-test is 30 and post-test is 88. The results of data analysis show that Z observed (2,05)> Z table 5% (1,96). It is concluded that Ha is accepted dan Ho is rejected. This means that there is a significant effect of the implementation of contextual learning on the ability to recognize Braille numbers of the blind children of TKLB of SLB-A YPAB Surabaya.   Keywords: Contextual Learning, Braille Numbers.